Increased risk of venous thromboembolism in hospitalized patients with cirrhosis due to non‐alcoholic steatohepatitis. Issue 3 (March 2018) - Stine, Jonathan G.; Niccum, Blake A.; Zimmet, Alex N.; Intagliata, Nicolas; Caldwell, Stephen H.; Argo, Curtis K.; Northup, Patrick G.
Abstract : Objective: : Patients with cirrhosis are at increased risk for venous thromboembolism (VTE) and portal vein thrombosis (PVT). Cirrhosis due to non‐alcoholic steatohepatitis (NASH) appears to be particularly prothrombotic. We investigated hospitalized patients with NASH cirrhosis to determine if they are at increased risk for VTE. Methods: : Data on adult hospitalized patients with cirrhosis and VTE (deep vein thrombosis and/or pulmonary embolism) between November 1, 2010 and December 31, 2015 were obtained. Cases with VTE were matched by age, gender, and model for end stage liver disease (MELD) score to corresponding controls without VTE. Results: : Two hundred and ninety subjects (145 matched pairs) with mean age of 58.4 ± 11.8 years and MELD score of 16.0 ± 7.2 were included. Baseline characteristics were similar between cases and controls. Independent adjusted risk factors for VTE included NASH (OR: 2.46, 95% CI: 1.07–5.65, p = 0.034), prior VTE (OR: 7.12, 95% CI: 1.99–25.5, p = 0.003), and presence of PVT (OR: 2.18, 95% CI: 1.03–4.58, p = 0.041). Thrombocytopenia was associated with decreased risk (OR: 0.49, 95% CI: 0.26–0.95, p = 0.035). Conclusions: : NASH is an independent risk factor for VTE among cirrhosis patients and provides further evidence that NASH is a hypercoagulable state. While all hospitalized patients with cirrhosis at risk for VTE should be considered for medical thromboprophylaxis, those with NASH cirrhosis are at particularly increased risk and therefore a high index of suspicion for VTE should be maintained even in the presence of thromboprophylaxis.